Kompetensi dan Motivasi Kerja Terhadap Kesiapan Mahasiswa Jurusan Akuntansi dalam Menghadapi Era Revolusi Industri 4.0 - Wiradarma, A. A Ngurah Bagus; Sari Widhiyani, Ni Luh (E-Jurnal Akuntansi, 2021)
The purpose of this study was to determine the effect of competence and work motivation on the readiness of students majoring in accounting in facing the era of the industrial revolution 4.0. This research was conducted at the Faculty of Economics and Business, Udayana University, Accounting Study Program. The number of samples taken was 167 students. The data analysis technique used to test the research hypothesis is multiple linear regression analysis. Based on the results of the analysis, it was found that competence and work motivation had a positive effect on student readiness. This shows that the higher the competence and work motivation of students, the higher the students' readiness to face the world of work in the era of the industrial revolution 4.0. This proves that student readiness is influenced by competence and work motivation which are very important for every profession. Keywords: Competence; Motivation; Student Readiness; Industrial Revolution Era 4.0.